STRES BELAJAR SISWA DALAM MELAKSANAKAN PEMBELAJARAN DARING PADA MASA PANDEMI - Mufarikah, Anis (Dharmas Education Journal (DE_Journal), 2022)
The background of this research is the online learning system makes learning motivation to decrease, as well as a lack of understanding of the material and short task processing time, causing learning stress. This research method is a survey research method with a quantitative approach. The population of this study were students of class IX MTs. Nurul Ulum Welahan totaling 80 students consisting of 5 classes, one class was used for try out, the sample consisted of one class which was used as the research sample. The total number of samples is 80 students. The sampling technique used is cluster random sampling technique. The analysis used to test the validity is product moment correlation and reliability using the alpha formula. The results of the questionnaire analysis can be concluded that most of the class IX students who attend school with online media at MTs. Nurul Ulum Welahan in the category of 7 students in the very low category with a percentage of 12%, 4 students in the low category with a percentage of 7%, 14 students in the high category with a percentage of 58%, and 11 students in the very high category with a percentage of 23%. Suggestions that researchers can convey in further research that discusses stress in students who attend school with online media. Further research is also expected to be able to discuss the factors that influence the level of stress in students who attend school with online media..